"We're Here, and We're Not Going Anywhere": De-Stigmatizing Voice Hearing in Community Mental Health. Issue 1 (2nd January 2023) - Goldstein, Benjamin
Abstract: This paper presents a case with a long-time voice hearer and patient with a diagnosis of schizophrenia in community mental health. The author shows how de-stigmatizing the experience of voice hearing, an approach offered in peer support models as well as in CBT for psychosis, works in tandem with a conceptualization of hallucinatory experiences informed by a Lacanian perspective outlined by Vanheule. Then, following theoretical formulations of Lacanian analysts Davoine and Gaudillière, the author discusses how psychotic phenomenon represent attempts at survival and the reconstruction of the world that has been lost. The author also draws out some barriers inherent in community-based treatment, specifically with regard to high staff turnover, and the difficulty of proper terminations in such settings given these limitations.